Analisis Determinan Belanja Modal dan Hubungannya Dengan PDRB (Studi pada Pemerintah Kabupaten/Kota di Provinsi Jambi) - Al Parok (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This study aims to analyze what are the determinant factors that influence capital expenditure and its relationship with GRDP. The determinant factors in this study consist of Local Own Revenue (PAD), Profit Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK), Other Legal Regional Income (LPS) and Remaining Surplus Budget Calculation (SiLPA). The object of this research is the Regency/City Government in Jambi Province. The method of analysis in this study uses panel data regression analysis. This analysis found that Local Own Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK), Other Legal Regional Income (LPS) and Budget Calculation Overtime (SiLPA) simultaneously affect capital expenditure and partially only Regional Original Income (PAD) Revenue Sharing Fund (DBH), General Allocation Fund (DAU) and Budget Calculation Overtime (SiLPA) have no effect on capital expenditure. Correlation analysis shows that capital expenditure has no significant relationship with GRDP. Keywords: Determinants of Capital Expenditure, Capital Expenditure and GRDP